Progressive Supranuclear Palsy–Parkinsonism Predominant (PSP-P): A Case Report - Ida Bagus Oka Garbhajana Sirinatha; D.P.G. Purwa Samatra; Sri Yenni Trisnawati (MEDICINUS, 2026)
Background: Progressive supranuclear palsy (PSP) is the most common form of atypical parkinsonism syndrome, presenting with signs and clinical features similar to Parkinson’s disease. The global incidence of PSP is estimated to be 0.005% of the world’s population, with 5% of those having parkinsonian symptoms or signs. PSP is a complex clinical disorder with a wide range of clinical manifestations that can lead to delayed diagnosis. Key symptoms of PSP include early postural instability, vertical saccadic eye movements, and vertical gaze palsy. Although no cure exists, early and accurate diagnosis is essential to optimize symptomatic management. Case: A 47-year-old female patient presented to the neurology clinic with stiffness throughout her body. The symptoms reportedly appeared suddenly 2 years ago and have worsened in the last 3 months. The patient also complained of slowed movement. Neurological examination revealed bradykinesia, postural instability, bidirectional nystagmus, and a decrease in cognitive function. The patient was diagnosed with progressive supranuclear palsy. The patient was managed with levodopa/carbidopa/entacapone (Stalevo®) 1 tablet every 12 hours and pramipexole 0.375 mg every 24 hours orally. Conclusion: A case of PSP–parkinsonism predominant (PSP‑P) in a 47-year-old female has been reported. The comparison with the existing literature supports the clinicalpresentation being consistent with PSP‑P.